How to assess authentic learning - Burke, Kay. 4 0 16; 5 (Thousand Oaks, California : Corwin Press, 2009)
Provides guidance and tools for alternative assessments that emphasize differentiating instruction, covering Response to Intervention (RTI) checklists, developing unit plans, creating portfolios, designing performance tasks, constructing rubrics, and other related topics.
Includes bibliographical references and index.
Professional.
Keywords: 2 -- 0; 6; Educational tests and measurements.;Grading and marking (Students);Grading and marking (Education); 20; 2